Ecologia comparativa dos lagartos Phyllopezus Periosus e Phyllopezus Pollicaris (Sauria: Phyllodactylidae) em simpatria em área de caatinga no Nordeste do Brasil - Freitas, Paulo Ragner Silva de (2013)
The dimensions in which species share resources can be classified into three general axis: food, habitat and time. The degree of sharing can be set indirectly throughout morphological differences, foraging mode and the use of space by sympatric species. This study presented two chapters, the first of which is entitled “Niche partitioning between the sympatric lizards Phyllopezus periosus and Phyllopezus pollicaris (Sauria: Phyllodactylidae) in a Caatinga area in northeastern Brazil”. We presented data on habitat use, perch height, period of activity, diet and morphology for both species. The second chapter was to focus on the “Demographic aspects of sympatric lizards Phyllopezus periosus and Phyllopezus pollicaris (Sauria: Phyllodactylidae) in a Caatinga area in northeastern Brazil”. In this chapter, we estimated the probability of survival (apparent survival), recapture probability and population density of P. periosus and P. pollicaris. Data collection was conducted in a Caatinga area (divided into sub-areas I, II and III) in the Salgadinho municipality, Paraíba State, from April 2012 to March 2013. The search for lizards occurred between 18:00 and 5:00 am of the following day. For each individual observed and/or captured, we recorded the following information: date and time of observation, microhabitat use, time, morphometric measurements, and gender. The marking of lizards was performed using Visible Implant Fluorescent Elastomer (polymer thick liquid that once applied subcutaneously, solidifies, however, remained flexible and visible). The analysis of apparent survival and recapture probability were performed using the model Cormack-Jolly Sebber (CJS), in the software MARK 6.2. Estimates of population density were calculated by the sums the individuals sighted, divided by the area (sub-area I) used in the study. Both species occupied predominantly saxicolous microhabitats, being observed a high overlap in the use of different microhabitats. The perch height preferentially used by P. periosus and P. pollicaris was 0 and 60 cm. However, P. periosus occupied higher perches (421 to 540 cm). The first individuals of both species were sighted from 18:02 until 04:29 hours of the the following morning. The two species showed no significant differences in the activity period. The more consumed prey by P. periosus were Coleoptera, Formicidae and Hemiptera, while the most consumed items for P. pollicaris were Coleoptera, Isoptera and Araneae. Phyllopezus pollicaris presented both the trophic niche breadth based on prey number and volume higher compared to P. periosus. However, the two species showed high overlap in their diets. We not observed differences in the volume of consumed prey. Both differed in body size and body mass, but adults of P. periosus and P. pollicaris showed no intraspecific differences in body size and body mass in relation to sex. Phyllopezus periosus presented a recapture rate of 30%, while P. pollicaris showed an average rate of 19%. Only Phyllopezus pollicaris showed variation in recapture rate over time, that it was negatively correlated with average rainfall of each month. The estimated survival in both species was constant over time. Phyllopezus periosus and P. pollicaris survival estimates showed 66% and 94%, respectively. P. pollicaris presented population density greater than P. periosus throughout the study. The highest densities observed for P. periosus were in July and November 2012, as for P. pollicaris were in the months of May and November of the same year. Both species showed variations in their population abundances depending on the sub-sampled area. While P. pollicaris was more abundant in sub-area I, P. periosus was more abundant in the sub-area III. Variations in population abundances between these two species may contribute to the coexistence of the two species in the area.